Improve the quality of the third age life with health-improving systems which based on elements of breathing exercises - Сибіль [Maria Sybyl] Марія Григорівна; Свищ [Yaroslav Svysch] Ярослав Степанович; Воронін [Denis Voronin] Денис Михаїлович; Кирилич [Maryana Kyrylych] Мар’яна Ігорівна (Slobozhanskyi Herald of Science and Sport, 2013)
<!–[if gte mso 9]> Normal 0 false false false RU X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> The aim of this study is the analysis of literary sources on the use of health systems containing elements of respiratory gymnastics to justify future experiment on introduction of the author’s Wellness program combines breathing exercises Bodyflex and breathing exercises Frolovs. The contingent of the experiment will be presented to the third age students at Lvov state University of physical culture. The Desk review confirmed the importance and necessity of searching the ways to improve the quality of the people of the third age life. This indicates the relevance of the scientific search for the experimental confirmation of the hypothesis on the application of innovative technology, based on combination of improving system Bodyflex and respiratory gymnastics Frolovs. <!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–><!–[if gte mso 10]> <![endif]–>